2009
DOI: 10.4318/tjg.2013.0540
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin based triple therapy versus standard clarithromycin based triple therapy in eradication of Helicobacter pylori infection in Iran: a randomized controlled clinical trial

Abstract: clarithromycin, amoxicillin, and omeprazole and azithromycin, amoxicillin, and omeprazole, respectively, and completed the study course. Per protocol, eradication rate was 83% with clarithromycin, amoxicillin, and omeprazole and 75% with azithromycin, amoxicillin, and omeprazole (p =0.158). Eradication rate for a subgroup of patients with peptic ulcer disease in two groups were 83% and 74%, respectively (p=0.134

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…During the previous years, four studies have evaluated the efficacy of azithromycin-containing regimens for H. pylori eradication, but none of these regimens could achieve acceptable eradication rates. 29 , 35 , 44 , 47 In 2006, Mousavi and colleagues assessed the efficacy of bismuth-based azithromycin-containing regimen in Semnan. 47 Also, in 2009, a subsequent study evaluated the efficacy of the same regimen in Tehran.…”
Section: Introductionmentioning
confidence: 99%
“…During the previous years, four studies have evaluated the efficacy of azithromycin-containing regimens for H. pylori eradication, but none of these regimens could achieve acceptable eradication rates. 29 , 35 , 44 , 47 In 2006, Mousavi and colleagues assessed the efficacy of bismuth-based azithromycin-containing regimen in Semnan. 47 Also, in 2009, a subsequent study evaluated the efficacy of the same regimen in Tehran.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Sarkeshikian et al ( 25 ), 165 adult patients with symptoms of dyspepsia were divided into two groups; the first group (89 patients) was treated with omeprazole, amoxicillin, and azithromycin and the second group (76 patients) with amoxicillin, omeprazole, and clarithromycin. According to the breath test performed 6 weeks later; the eradication rate was 75% in the first group and 82% in the second group, and there was no statistically significant difference between the two groups ( 25 ). This study was consistent with our study regarding the lack of significant difference in the therapeutic response between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Out of three 7-d regimens, 1 study showed acceptable eradication rates [19][20][21] . Also, out of three 10-d regimens, 2 were successful in achieving > 90% PP eradication rate [22][23][24] and out of three 14-d regimens, 1 yielded optimal results [25][26][27] .…”
Section: Standard Triple Therapymentioning
confidence: 99%